2018
DOI: 10.1021/acs.inorgchem.7b03175
|View full text |Cite
|
Sign up to set email alerts
|

1,2,4-Triazines in the Synthesis of Bipyridine Bisphenolate ONNO Ligands and Their Highly Luminescent Tetradentate Pt(II) Complexes for Solution-Processable OLEDs

Abstract: This article describes a convenient method for the synthesis of ONNO-type tetradentate 6,6′-bis(2-phenoxy)-2,2′-bipyridine (bipyridine bisphenolate, BpyBph) ligands and their platinum(II) complexes. The methodology includes the synthesis of 1,2,4-triazine precursors followed by their transformation to functionalized pyridines by the Boger reaction. Two complementary routes employing 3,3′-and 5,5′bis-triazines allow a modification of the central pyridine rings in different positions, which was exemplified by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“… d Photoluminescence quantum yield recorded using tetraphenylporphyrin in air-equilibrated acetonitrile as the standard, Φ PL = 0.075. 34,35 e Photoluminescence lifetime. f TADF radiative rate constant calculated assuming that the emissive state is formed with unit efficiency: k TADF r = Φ PL / τ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… d Photoluminescence quantum yield recorded using tetraphenylporphyrin in air-equilibrated acetonitrile as the standard, Φ PL = 0.075. 34,35 e Photoluminescence lifetime. f TADF radiative rate constant calculated assuming that the emissive state is formed with unit efficiency: k TADF r = Φ PL / τ .…”
Section: Resultsmentioning
confidence: 99%
“… d Photoluminescence quantum yield recorded using tetraphenylporphyrin in air-equilibrated acetonitrile as the standard, Φ PL = 0.075. 34,35 …”
Section: Resultsmentioning
confidence: 99%
“…Pilot experiments indicated that complete Pt 2+ /Mn 2+ exchange was obtained after 5 days of incubation at room temperature. The long incubation time needed is presumably due to slow Pt 2+ exchange kinetics 19,20 and steric hindrance in the hexa-dendate MnDPDP complex. The steric hindrance of naked DPDP or CaDPDP (where Ca 2+ is loosely bound to DPDP) is anticipated to be considerably lower.…”
Section: Methodsmentioning
confidence: 99%
“…This compound is an important starting material for preparation of other coordination complexes of Pt 2+ aimed for e.g., medical use. Although the chloride ligands of [PtCl 4 ] 2− are displaced by many other ligands, the ligand-exchange behavior of Pt(II)complexes is quite slow, which gives them a high kinetic stability 20 and results in ligand-exchange reactions of minutes to days, rather than microseconds to seconds for many other coordination compounds 19 .…”
Section: Introductionmentioning
confidence: 99%
“…216,217 More recently, Pt(II), Zn(II), Cu(I) and other transition complexes have been used as materials for OLEDs. [218][219][220][221] In the limited scope of this perspective, it is not possible to do justice to the wide range of transition metal complexes which are being explored in the world of OLEDs. Hence, we have restricted our discussion to a general description of design principles and a few specific examples of transition metal complex incorporated in OLEDs.…”
Section: Oledsmentioning
confidence: 99%